A comparative evaluation of peppermint oil and lignocaine spray as topical anesthetic agents prior to local anesthesia in children: a randomized clinical trial - Petluru, Harika; Nirmala, SVSG; Nuvvula, Sivakumar (Journal of Dental Anesthesia and Pain Medicine, 2024)
In pediatric dentistry, fear and anxiety are common among children. Local anesthetics (LA) are widely used to control pain and reduce discomfort in children during dental treatment. Topical anesthetics play a vital role in reducing pain and the unpleasant sensation of a needle puncture in children. Peppermint oil has been extensively used for various diseases. However, its anesthetic properties remain unknown. Peppermint oil, used in mouthwashes, toothpastes, and other topical preparations has analgesic, anesthetic, and antiseptic properties. This study aimed to compare and evaluate pain perception following the topical application of peppermint oil versus lignocaine spray before an intraoral injection in children, aged 8-13 years. Fifty-two children, aged between 8-13 years, who required local anesthesia for dental treatment were divided into two groups of 26 each by simple random sampling (Group 1: 0.2% peppermint oil and Group 2: lignocaine spray). In both groups, physiological measurements (e.g., heart rate) were recorded using pulse oximetry before, during, and after the procedure. Objective pain measurement (Sound Eye Motor (SEM) scale) during administration and subjective measuremeant (Wong-Baker Faces Pain Rating Scale (WBFPRS)) after LA administration were recorded. This was followed by the required treatment of the child.Physiological parameters were compared between the two groups using an independent t-test for intergroup assessment and a paired t-test and repeated-measures ANOVA for intragroup comparisons. The Mann-Whitney U test was used to analyze the pain scores. Intragroup mean heart rates, before, during, and after treatment were statistically significantly different (P < 0.05). However, the intergroup mean pulse rates did not differ significantly between the two groups. The mean WBFPS score in the lignocaine spray group was 4.133 ± 2.06 was statistically different from that of the peppermint oil group (0.933 ± 1.03; P < 0.001 ). The mean SEM score was significantly lower in the peppermint oil group than that in the lignocaine spray group (P = 0.006). No negative effects were observed in this study. 0.2% peppermint oil was effective in reducing pain perception.